DNS log analysis system based on big data fusion algorithm - Ming LIAO; Ming CHEN; Ji ZHOU; Xiaohua XIANG; Fang LI; Yefen JIAO (Dianxin kexue)
The existing problems of big data analysis of DNS logs in the current industry were summarized,and a DNS log analysis system based on big data fusion algorithm was designed.The system integrates six information databases,such as record information database,website database,domain name database,IP address database,CNAME domain name database and security information database.It has powerful log analysis performance,comprehensive content analysis,and classification.With high analysis depth and flexible report customization function,it can provide decision-making basis for telecom operators to improve the management efficiency,optimize network security and enhance the network rate.